Implied licences in copyright law - Mysoor, Poorna, 1975- (Oxford : Oxford University Press, 2021)
Poorna Mysoor's book develops a systematic way of implying copyright licences and analyses the existing case law in light of these proposed frameworks to demonstrate how the court's reasoning can be made methodical and transparent, testing the methodology in relation to three essential functions on the internet - browsing, hyperlinking and indexing.
This edition also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 10, 2021).
Keywords: Copyright